English teachers’ perception and attitudes of scaffolding method in teaching academic writing: An exploratory study at universities in Vietnam - Mai, Nguyen Ban; Hien, Ta Huu; Phuong, Nguyen Le Tuong (Journal of Education and e-Learning Research, 2023)
The primary aim of this research is to investigate the impact of utilizing the scaffolding method on teaching academic writing in the context of English as a Foreign Language (EFL) at universities in Vietnam. This mixed-method study examined the attitudes and perceptions of 88 EFL educators from diverse backgrounds and degree levels who were randomly selected for the research. Methodologically, data were gathered and analyzed using the appropriate methods for each instrument, including a questionnaire and focus group discussion (FGD). Theoretically, the study is a medley of relevant theories and approaches such as Vygotsky’s Sociocultural Theory of Learning, the Scaffolding theory, and the ‘High challenge - High support’ pedagogy. The results of this study suggest that participants used scaffolding to some extent and had strongly positive attitudes and perceptions regarding its practical aspects; however, the findings also revealed that the surveyed lecturers are deficient in the necessary knowledge and skills. In addition, the study's findings imply that EFL teachers need training on how to properly use scaffolding as a pedagogical strategy to facilitate teaching academic writing to EFL students.